Dracolestes Goin, Candela, Abello, and Oliveira, 2009, is a Nomen nudum - Goin, Francisco Javier (2012)
Goin et al. (2009) described the oldest Paucituberculata marsupials from the Las Flores and La Barda localities of Argentina (Late Palaeocene, and Early?Middle Eocene), as well as from the Itaboraí Basin of Brazil (Late Palaeocene). The new taxa, represented by very scarce, although well-preserved, dental remains were named Riolestes capricornicus, Bardalestes hunco, and Bardalestessp. Notwithstanding, these authors named Dracolestessp. the specimen MLP 90-II-5-300 (Goin et al., 2009, Table 1: p. 871), and also designated Dracolestesas a Plesion of the Order Paucituberculata (Goin et al., 2007, Table 3: p. 879). According to Goin et al. (2009) the specimen MLP 90-II-5-300 is an isolated right talonid that was illustrated and named Bardalestessp. in Fig. 2 E-F (p. 869). This specimen, as well as the specimens MLP 90-II-5-336,MLP 90-II-5-335, MLP 90-II-5-337. were the four referred specimens of Bardalestessp. (p.873), and were described on pages 873-874 of Goin et al. (2009). According to the above-mentionedevidences, the name DracolestesGoin, Candela, Abello and Oliveira 2009 fails to conform to Article 13 of the International Code of Zoological Nomenclature (ICZN, 2000), because Dracolesteswas not ??accompanied by a description or definition that states in words characters that are purported to differentiate the taxon? (Art. 13.1.1, ICZN, 2000). Dracolestesis a nomen nudumand, consequently, is not an available name. Notwithstanding, Dracolestes??may be made available later for the same or a different concept; in such a case it would take authorship and date [Arts. 50, 21] from that act of establishment, not from any earlier publication as a nomen nudum? (ICZN, 2000: Glossary). An internet inside the ?Index to Organism names? (ION, 2008) and Google Scholar ({{Google scholar cite|keywords=dracolestes}}) revealed that the name Dracolestes has not been used or cited in the scientific literature after the paper of Goin et al. (2009).